Important nesting habitats of olive ridley turtles Lepidochelys olivacea along the Andhra Pradesh coast of eastern India - Tripathy, Basudev; Shanker, Kartik; Choudhury, B. C. (Oryx, 2003)
Olive ridley turtles Lepidochelys olivacea nest along the east and west coasts of India, with major mass nesting beaches in the state of Orissa. The coast of Andhra Pradesh, the state immediately south of Orissa, has sporadic nesting of olive ridley turtles and is believed to form part of the migratory route of the turtles that nest in Orissa. A survey of nesting beaches and offshore waters of the Andhra Pradesh coast was carried out from November 2000 to April 2001. Preliminary interviews and secondary data were used to determine potential nesting beaches. During January–March 2001 intensive surveys of seven beaches and monthly surveys of the rest of the coast provided a lower bound of c. 4,000 nests along the Andhra Pradesh coast. Nesting densities were higher at beaches near river mouths, at 60–100 nests km−1 in northern and central Andhra Pradesh, and 15–20 nests km−1 in southern Andhra Pradesh. Sightings and incidental catch in experimental trawls indicated the presence of olive ridley turtles in offshore waters. Fisheries related mortality is the major threat to the species, with nearly 1,000 dead turtles being washed ashore during January–March, but depredation of eggs by humans and feral animals was also widespread. Conservation efforts need to address these issues, and also the effects of coastal development and artificial illumination, especially at beaches that support relatively high densities of nesting olive ridley turtles.